The answer is 1761 1/2 (1761.5 in decimal form)
-- Reflecting across the x-axis makes all the x-coordinates the negative of
what they were before the reflection. The y-coordinates don't change.
-- Translating 2 units up makes all the y-coordinates 2 greater than
they were before the translation. The x-coordinates don't change.
You didn't give us a list of new coordinates, so there's nothing
to match with.
Because -2 3/4 is on the x axis, it is the diagonal one, -4 1/2 is on the y axis it’s vertical.
The first number is x, the second is y.
Brainliest answer please?
Since .68 is 68/100, you can simplify to 17/25.
Answer:
![y=\dfrac{1}{1-Ke^{-t}}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B1%7D%7B1-Ke%5E%7B-t%7D%7D)
Step-by-step explanation:
Given
The given equation is a differential equation
![\dfrac{dy}{dt}=y-y^2](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdt%7D%3Dy-y%5E2)
![\dfrac{dy}{dt}=-(y^2-y)](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7Bdt%7D%3D-%28y%5E2-y%29)
By separating variable
⇒![\dfrac{dy}{(y^2-y)}=-t](https://tex.z-dn.net/?f=%5Cdfrac%7Bdy%7D%7B%28y%5E2-y%29%7D%3D-t)
![\left(\dfrac{1}{y-1}-\dfrac{1}{y}\right)dy=-dt](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7B1%7D%7By-1%7D-%5Cdfrac%7B1%7D%7By%7D%5Cright%29dy%3D-dt)
Now by taking integration both side
![\int\left(\dfrac{1}{y-1}-\dfrac{1}{y}\right)dy=-\int dt](https://tex.z-dn.net/?f=%5Cint%5Cleft%28%5Cdfrac%7B1%7D%7By-1%7D-%5Cdfrac%7B1%7D%7By%7D%5Cright%29dy%3D-%5Cint%20dt)
⇒![\ln (y-1)-\ln y=-t+C](https://tex.z-dn.net/?f=%5Cln%20%28y-1%29-%5Cln%20y%3D-t%2BC)
Where C is the constant
![\ln \dfrac{y-1}{y}=-t+C](https://tex.z-dn.net/?f=%5Cln%20%5Cdfrac%7By-1%7D%7By%7D%3D-t%2BC)
![\dfrac{y-1}{y}=e^{-t+c}](https://tex.z-dn.net/?f=%5Cdfrac%7By-1%7D%7By%7D%3De%5E%7B-t%2Bc%7D)
![\dfrac{y-1}{y}=Ke^{-t}](https://tex.z-dn.net/?f=%5Cdfrac%7By-1%7D%7By%7D%3DKe%5E%7B-t%7D)
![y=\dfrac{1}{1-Ke^{-t}}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B1%7D%7B1-Ke%5E%7B-t%7D%7D)
from above equation we can say that
When t will increases in positive direction then
will decreases it means that
will increases, so y will decreases. Similarly in the case of negative t.